OYO Rooms: Their Hospitality and Customer Satisfaction - Sharma, Shobha; Nidhi, Nidhi; Pathak, Smita; Pandey, Rudresh; Tianen, Wang; Hung, Daisy Kee Mui; XiaoLin, Huang; Xuan, Wang Ying; Rana, Virat; Naresh, Prudhvi; P.V, Ranjith (AIBPM Publisher, 2020)
The study is being done on the problems faced by the hospitality and tourism industries. Their growth and development. But here the research is done specifically in respect to OYO. The objective here is to tell the growth story of OYO room in the most objective way possible as a